Multitrafo-app: Web app for project of 18-pulses rectifiers with differential transformer connections - Oliveira, P. S.; Freitas, S. C.L.; Silva, T. M.; Seixas, F. J.M. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2016)
This paper presents a Web Application proposal to simulate and design 18-pulses rectifiers, which uses Wye and Delta differentials autotransformer connections. In this tool, it is possible to get the main waveforms of voltage and current for these rectifiers as well as the possible connections of the autotransformer windings for different average voltage values in charge. The application will also generate all the values of voltages and currents in the autotransformer windings, and project values, as core size, number of turns for the windings. It will also generate some parameters related to power quality of this equipment such as power factor and total harmonic distortion of current. Soon, it is expected that, in a didactic way, this tool assists students and engineers to increase knowledge of this type of topology and enable them to implement these rectifiers through the design data that the application will provide.
Keywords: Differential connections Multipulse rectifiers; Web application